2013
DOI: 10.1371/journal.pone.0077757
|View full text |Cite
|
Sign up to set email alerts
|

Subjective Motives for Requesting In-Patient Treatment in Female with Anorexia Nervosa: A Qualitative Study

Abstract: BackgroundAnorexia nervosa is a severe psychiatric disorder mainly affecting women. Its treatment is long and accepted with much difficulty, in particular in-patient treatment.AimsTo describe the subjective motives of women with anorexia nervosa for requesting in-patient admission, from a qualitative analysis of application letters.MethodsParticipants were adult women (18 years and older) with anorexia nervosa who were admitted as in-patients in a referral hospital unit in France from January 2008 to December … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
33
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(34 citation statements)
references
References 31 publications
0
33
0
1
Order By: Relevance
“…on the other hand, the concept as such could possibly also serve to promote the kind of selfknowledge that is needed in order to be able to utilize it and, by extension, foster skills and coping mechanisms that could influence the course and prognosis of the disorder itself. Gorse et al (35) have shown that patients suffering from anorexia nervosa request inpatient treatment after the initial period of reinforcement inherent to the disorder has passed, and that this is part of a personal process of increased awareness; such a process could very well be further modified by allowing patients to take more responsibility for their own recovery and fostering reflection on motives and barriers in asking for help. A patient-controlled admission model is now being studied at the stockholm Centre for eating disorders.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…on the other hand, the concept as such could possibly also serve to promote the kind of selfknowledge that is needed in order to be able to utilize it and, by extension, foster skills and coping mechanisms that could influence the course and prognosis of the disorder itself. Gorse et al (35) have shown that patients suffering from anorexia nervosa request inpatient treatment after the initial period of reinforcement inherent to the disorder has passed, and that this is part of a personal process of increased awareness; such a process could very well be further modified by allowing patients to take more responsibility for their own recovery and fostering reflection on motives and barriers in asking for help. A patient-controlled admission model is now being studied at the stockholm Centre for eating disorders.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…Crossing the perspectives of patients, families, and healthcare providers enables a better understanding of their shared representations of the disease and its treatment. In recent years we have conducted several qualitative studies exploring the intersecting viewpoints around the issues of obesity [21] and attempted suicide [22] in pediatric populations as well as on the topics of cancer [23] and AN [24] in adults.…”
Section: Introductionmentioning
confidence: 99%
“…For individuals with severe AN, issues regarding isolation and poor social support may be particularly poignant. Gorse et al [ 18 ] identify isolation as being a reason cited by individuals with AN for seeking hospital treatment, and inpatient care may become iatrogenically reinforcing by temporarily reducing isolation [ 19 ]. Individuals with severe and enduring AN report poor quality of life, particularly in the domains of interpersonal avoidance, with the illness having a negative impact on social life [ 20 ].…”
Section: Introductionmentioning
confidence: 99%